2019
DOI: 10.3390/jcm8060763
|View full text |Cite
|
Sign up to set email alerts
|

Value of Somatostatin Receptor Scintigraphy with 99mTc-HYNIC-TOC in Patients with Primary Sjögren Syndrome

Abstract: Objectives: Primary Sjögren syndrome (SS) is diagnosed based on the American European Consensus Group (AECG) criteria, but lacks specificity, not only in the involvement of salivary glands, but also in extra-glandular involvement. Whole-body somatostatin receptor scintigraphy with 99mTc-HYNIC-TOC scintigraphy could overcome these limitations. The aims of this study were to evaluate salivary gland uptake of 99mTc-HYNIC-TOC in untreated patients with de-novo diagnosis of SS as compared to control subjects and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Hence, 68 Ga-DOTA-TATE uptake was not recorded in the brain parenchyma. The salivary glands, including the parotid and submandibular glands, demonstrated diffuse and homogenous uptake of 68 Ga-DOTA-TATE, which is expected as Anzola et al ( 16 ) demonstrated that SSTRs are commonly expressed in the salivary glands.…”
Section: Discussionmentioning
confidence: 63%
“…Hence, 68 Ga-DOTA-TATE uptake was not recorded in the brain parenchyma. The salivary glands, including the parotid and submandibular glands, demonstrated diffuse and homogenous uptake of 68 Ga-DOTA-TATE, which is expected as Anzola et al ( 16 ) demonstrated that SSTRs are commonly expressed in the salivary glands.…”
Section: Discussionmentioning
confidence: 63%
“…These receptors were shown to be overexpressed in various inflammatory and autoimmune diseases, and were found on, among others, activated lymphocytes, endothelial cells, and the monocyte lineage in synovium of rheumatoid arthritis (RA) patients [ 94 , 95 , 96 ]. Anzola et al [ 97 ] showed increased 99m Tc-HYNIC-TOC uptake within salivary glands of pSS patients compared to controls, as well as a considerably higher sensitivity of 99m Tc-HYNIC-TOC scintigraphy compared to conventional scintigraphy. Furthermore, they demonstrated that 99m Tc-HYNIC-TOC scintigraphy was able to identify joint involvement in a cohort of 62 pSS patients, of which many patients (87%) reported joint pain.…”
Section: Nuclear Medicine Techniquesmentioning
confidence: 99%
“…This was the subject of the Anzola [25] research whose results were published in 2019. In this study scintigraphy with 99m Tc-HYNIC-TOC as well as conventional sialoscintigraphy with 99m TcO4was performed on patients with de-novo diagnosis of pSS and control subjects.…”
Section: Scintigraphymentioning
confidence: 99%
“…In this study scintigraphy with 99m Tc-HYNIC-TOC as well as conventional sialoscintigraphy with 99m TcO4was performed on patients with de-novo diagnosis of pSS and control subjects. The examination made it possible to identify active inflammatory processes not only in the salivary glands of pSS patients, but also in the joints [25].…”
Section: Scintigraphymentioning
confidence: 99%